Occupational Violence against Brazilian Nurses - Alessandro Leite CAVALCANTI; Eduardo dos Reis BELO; Emanuella de Castro MARCOLINO; Américo FERNANDES; Yuri Wanderley CAVALCANTI; Danielle Franklin de CARVALHO; Ana Maria Gondim VALENÇA; Alidianne Fabia Cabral CAVALCANTI; Wilton Wilney Nascimento PADILHA (Tehran University of Medical Sciences, 2018)
Background: We evaluated the prevalence and risk factors of workplace violence against Brazilian nurses in 2014. Methods: The study's population comprised of 112 nurses working in teams of Family Primary Care Units and Primary Care Health Centers. Those nurses were asked to answer a questionnaire that addressed the socio-demographic information, the professional routine and the occupational violence faced (types, frequency and characteristics of perpetrators). Data were analyzed using the SPSS software. Results: Most of nurses were female (94.6%), aged between 34-43 yr (38.4%), living with a partner (60.7%) and having a weekly workload of 40 h (90.1 %). The prevalence of violence was 73.2%. Predominantly, occupational violence comprised of verbal violence (67.0%) and psychological harassment (bullying -27.1%). Patients (81.1%) and caregivers (83.1%) were responsible for verbal violence, whilst the heads of teams (78.3%) and other health professionals (41.7 %) practiced bullying. The risk factors more frequently reported were the lack of safety in the workplace (73.2%) and the aggressive behavior of patients (67%). The occupational violence was not statistically associated with the gender, professional experience, experience at primary health care, weekly working hours, or working shift. The type of violence faced was not either statistically associated with gender, marital status, professional experience, weekly working hours, or working shift. Conclusion: Occupational violence has high prevalence among Brazilian nurses working at primary health care system. Verbal violence is more prevalent and frequently practiced by patients. The lack of safety in the workplace is the main risk factor associated with occupational violence faced by nurses.